MENEGUHKAN INKLUSIVISME AHL DZIMMAH DAN KAWIN BEDA AGAMA (UINSI Samarinda, 2012)
Fiqh constructed earlier scholars not only to future or after the jurisprudence is not codified but also to accommodate a growing tradition in the past. Usually refers only to the scholars of fiqh scholars earlier opinion or just take a verse and a tradition to serve as justification and legitimacy. Growing humanitarian problems and knowledge have made progress, the inevitable renewal of jurisprudence to be an alternative solution. Fiqh scholars see the importance of re-opening of classical fiqh is not critical in terms of overhaul, but in terms of jurisprudence update to address several problems that continue to evolve. Assessing the activity of jurisprudence sometimes get stuck in a puddle of fatalism that the discourse of jurisprudence which was originally an open and diverse in the region eventually entered politics and efforts to the struggle for authority.